Effectiveness of an Educational Program on Nurse's knowledge concerning Complications of Cardiac Catheterization among Children at Al-Nassirhya Heart Center - Leila Fakhir Aburaghif; Nadhem Kaser Hassan (Kufa Journal for Nursing Sciences)
OBJECTIVE: To assess nurses' knowledge concerning complications of cardiac catheterization among children and to find out the relationships between the nurses' knowledge concerning complications of cardiac catheterization among children and socio-demographic information.